Pengaruh Keselamatan Dan Kesehatan Kerja Terhadap Kinerja Karyawan Bagian Gudang Pada PT. Kelian Mitra Karya Pekanbaru - Syafrina, Nova (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
This study aims to determine the effect of occupational safety and health on the performance of warehouse employees at PT Kelian Mitra Karya Pekanbaru. In this study, data were collected through questionnaires to 33 people. The data analysis technique used was multiple regression analysis which serves to prove the research hypothesis. The results of multiple regression show the value of Sig. Amounting to 0.000 <0.05, at an error rate of 5% and an F_count value of 10.107, it can be concluded that safety and health together have a significant influence on the performance of warehouse employees at PT Kelian Mitra Karya Pekanbaru. The t value for the work safety variable is 1.554 while the t table value is 2.039. it can be concluded that work safety has no significant effect on the performance of warehouse employees at PT Kelian Mitra Karya Pekanbaru. And the t value for work health is 4.036 while for the t table value is 2.039. it can be concluded that occupational health has a significant effect on the performance of warehouse employees at PT Kelian Mitra Karya Pekanbaru. The Adjuster R Square value of 0.363 means that the magnitude of the influence of safety and health on the performance of warehouse employees at PT Kelian Mitra Karya Pekanbaru is 36.30%.